Conceptualisations and perceptions of the nurse preceptor's role: A scoping review. (January 2016) - Trede, Franziska; Sutton, Katelin; Bernoth, Maree
Summary: Objectives: The practice of nursing is a substantially different undertaking to supervising nursing students. A clear conceptualisation of the preceptor role reveals its scope, expectations and responsibilities. The aim of this scoping review is to investigate what is known in the pertinent literature about preceptors' experiences of their supervision practices and their perceptions of what makes a good workplace environment that enables good preceptorship and is conducive to student learning. Design and Data Sources: The literature scoping review design by Arksey and O'Malley was adopted for this literature review study because it enables researchers to chart, gather and summarise known literature on a given topic. Databases searched included Scopus, Ebsco, Informit and VOCEDplus. Review Method: To answer our research question what is known about how undergraduate nursing student preceptors' supervision practices are conceptualised and perceived we posed four analysis questions to our literature set: (1) How do the articles conceptualise preceptorship? (2) What pedagogical frameworks are used to understand preceptorship? (3) What are the messages for preceptorship practices? (4) What are the recommendations for future research? Results: A total of 25 articles were identified as eligible for this study. The results are ordered into four sections: theoretical conceptualisations of the preceptorship role, pedagogical framework, messages about preceptoring and recommendations for further research. Conclusion: The discourse of preceptorship is not underpinned by a strong theoretical and pedagogical base. The role of preceptors has not been expanded to include theoretical perspectives from socio-cultural practice and social learning paradigms. Highlights: There is a need to move away from individual preceptor accountability approaches. Good preceptorship is a reciprocal, agentic and shared responsibility. Positive learning environments are achieved by cultural and collective efforts. Preceptorship is not underpinned by a strong theoretical and pedagogical base. Conceptualisations of preceptorship within a socio-cultural perspective are needed.